2010
DOI: 10.1091/mbc.e10-08-0705
|View full text |Cite
|
Sign up to set email alerts
|

C-junInhibits Mammary Apoptosis In Vivo

Abstract: c-Jun mediates ROS production and apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 48 publications
1
24
0
1
Order By: Relevance
“…JNK activation was found to be in parallel with phosphorylation of c-Jun. Previous studies have reported that c-Jun activation has pro-hypertrophic and pro-apoptotic effects (16,32,52). In this study, an increase in JNK-dependent phosphorylation of c-Jun in pressure-overloadinduced heart failure was significantly decreased by SUMO-1 overexpression.…”
Section: Sumo-1 Overexpression Contributes Toward Regulating Redox Sisupporting
confidence: 55%
See 1 more Smart Citation
“…JNK activation was found to be in parallel with phosphorylation of c-Jun. Previous studies have reported that c-Jun activation has pro-hypertrophic and pro-apoptotic effects (16,32,52). In this study, an increase in JNK-dependent phosphorylation of c-Jun in pressure-overloadinduced heart failure was significantly decreased by SUMO-1 overexpression.…”
Section: Sumo-1 Overexpression Contributes Toward Regulating Redox Sisupporting
confidence: 55%
“…c-Jun activity is also closely associated with MnSOD transcripts and its activity. Endogenous c-Jun represses ROSreducing genes such as MnSOD and catalase via mitochondrial complexes and Nox enzyme (32).…”
Section: Sumo-1 Overexpression Contributes Toward Regulating Redox Simentioning
confidence: 99%
“…In fact, the binding of AP-1 to cellular extracts progressively decreases in cells incubated with increasing concentrations of CAT, as well as the activity of 3TP-Lux construction, which specifically activates in response to AP-1. This was a rather expected result, as this factor seems to be one of the most relevant transcription factors involved in TGF-ÎČ1 regulation (16,30), and it is up-regulated by ROS over-production (14,21,30,38).…”
Section: Discussionmentioning
confidence: 71%
“…Acetylation of MnSOD directs the enzymatic activity responding to cellular nutrient status or oxidative stress (157). JNK-mediated repression of MnSOD and catalase occur via mitochondrial complex I and NOX I (104). Among the main factors involved in the redox balancing in adaptive response to IR (119), ATM, NF-jB, and pre-inflammatory factors (134,135,224) may also be regulated via NOX (220).…”
Section: Fig 3 Cyclin D1 Interacts Withmentioning
confidence: 99%